MENINGOCOCCUS GROWTH STIMULATORS FOR MENINGITIS DIAGNOSTICS BASED ON 2-HYDROXYLALKYLAMINE SALTS - A. N. Mirskova; S. N. Adamovich; E. Ya. Vinogradov; R. G. Mirskov (Acta Biomedica Scientifica)
The methods for the synthesis of 4-(4 '-nitrophenyl)-L-(+)-treo- and 2,8-dimethyl-4-(4 '-nitro-phenyl)-L-(+)-treo- 1-aza-3,7-dioxabicyclo-[3,3,0]octanes as well as iodomethylates of L-(+)-treo-, D-(-)-treo- and. D-(-)-, L-(+)-treo -4-(4 '-nitrophenyl)-1-aza-3,7-dioxabicyclo-[3,3,0]-octanes have been developed. It has been shown for the first time that optically isomeric iodo-methylates of 4-(4 '-nitrophenyl)-1-aza-3,7-dioxabicyclo[3,3,0]octanes possess high growth-stimulating activity with respect to meningococcus strains isolated from cerebrospinal fluid of patients thus indicating the possibility of these compounds application for qualitative diagnostics of meningitis. A method for the preparation of elective «Dry medium nutritium. ad. meningococcos siccum» for isolation and. cultivation of meningococci has been elaborated. Methods for the synthesis of novel potential stimulators of microorganisms growth have been worked out on the basis of biologically active aryloxy(arylsulfanyl)acetic acids and. waste of Levomecytin (Chloramphenicol) production, «L-treoamine».